Apelin targets gut contraction to control glucose metabolism via the brain. Issue 2 (12th November 2015) - Fournel, Audren; Drougard, Anne; Duparc, Thibaut; Marlin, Alysson; Brierley, Stuart M; Castro, Joel; Le-Gonidec, Sophie; Masri, Bernard; Colom, André; Lucas, Alexandre; Rousset, Perrine; Cenac, Nicolas; et al.
Abstract : Objective: The gut–brain axis is considered as a major regulatory checkpoint in the control of glucose homeostasis. The detection of nutrients and/or hormones in the duodenum informs the hypothalamus of the host's nutritional state. This process may occur via hypothalamic neurons modulating central release of nitric oxide (NO), which in turn controls glucose entry into tissues. The enteric nervous system (ENS) modulates intestinal contractions in response to various stimuli, but the importance of this interaction in the control of glucose homeostasis via the brain is unknown. We studied whether apelin, a bioactive peptide present in the gut, regulates ENS-evoked contractions, thereby identifying a new physiological partner in the control of glucose utilisation via the hypothalamus. Design: We measured the effect of apelin on electrical and mechanical duodenal responses via telemetry probes and isotonic sensors in normal and obese/diabetic mice. Changes in hypothalamic NO release, in response to duodenal contraction modulated by apelin, were evaluated in real time with specific amperometric probes. Glucose utilisation in tissues was measured with orally administrated radiolabeled glucose. Results: In normal and obese/diabetic mice, glucose utilisation is improved by the decrease of ENS/contraction activities in response to apelin, which generates an increase in hypothalamic NO release. As a consequence, glucose entry is significantly increased in the muscle. Conclusions: Here, we identify a novel mode of communication between the intestine and the hypothalamus that controls glucose utilisation. Moreover, our data identified oral apelin administration as a novel potential target to treat metabolic disorders.